Investigating and Evaluating Accounting Educational Resources with A Swot Approach In Iranian Conservatories - Jazini Zadeh, Somayeh; Sotudeh, Reza; Haghparast, Abbasali; Hirad, Alireza (Business, Marketing, and Finance Open, 2024)
The present study was conducted with the aim of investigating and evaluating accounting educational resources in Iranian conservatories using a SWOT approach. The present study evaluated accounting educational resources in Iranian conservatories using a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). This research method included collecting data through semi-structured questionnaires, specialized interviews with conservatories’ teachers and administrators, and studying the content of textbooks. Data analysis was conducted with the aim of identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats). Subsequently, to formulate appropriate strategies, the results of the SWOT analysis were used in such a way that strengths are strengthened, weaknesses are reduced, opportunities are exploited, and threats are minimized. This study was conducted by collecting the opinions of accounting teachers through an online questionnaire and analyzing the content of specialized and skill books. The results showed that the research findings showed that the educational resources of the accounting field in Iranian art schools have strengths such as providing basic concepts, strengthening practical skills, and providing appropriate infrastructure for teaching financial and accounting laws. However, these resources face several challenges, including inappropriate arrangement of chapters, complexity of the content of some modules, and lack of updating based on current laws and standards. In addition, the high volume of unnecessary and stereotypical materials reduces the motivation of students. In contrast, opportunities such as localization of content, inclusion of specialized software training, and utilization of modern educational technologies can improve the quality of education. However, threats such as student apathy, limited technological infrastructure, and rapid changes in financial laws and accounting standards still pose significant challenges. To address these challenges, a comprehensive review of educational resources, removal of unnecessary materials, and increase in applied training seem necessary. Finally, it is suggested that a comprehensive review of educational resources, training teachers to utilize modern technologies, and simplifying course content be put on the agenda in order to improve the quality of accounting education in Iranian technical schools.